Effect adding powder of radish seeds and neomycin to chicken feed mixtures in some blood, biochemical and immunological indicators (Journal of Hama University, 2020)
This study was conducted by using 165 Ross 308, The birds were divided into five groups with three replicates per group, the first group was control G1, the second group G2 was added to the neomycin antibiotic with 200 mg / kg feed In the third (R1), fourth(R2) and fifth(R3) groups,which added radish seeds at percentage 0.5%, 0.75%, and 1%., The following blood and biochemical parameters were studied: the number of red blood cells , Hemoglobin , number of white blood cells ,glucose , protein , Albumin, Globulin and cholesterol. antibody against the Newcastle virus measure by ELISA test.The results indicated that the addition of radish seeds led to a significant increase in the concentration of blood protein and blood globulin. Also, the addition of radish seeds resulted in a significant decrease in sugar and cholesterol of blood . Positive changes were also observed in blood indices. Hemoglobin and red blood cells increased, (P